Improving the competitive advantage through information technology: A case at food and beverage industries in Indonesia - Musran Munizu (Journal of Economics, Business, and Accountancy Ventura, 2014)
This study attempts to investigate the effect of Information Technology (IT) on competitive advantage, especially food and beverage industry in South Sulawesi, Indonesia. The research used survey approach and the data were collected by questionnaire. The unit of analysis is big and medium scale companies. The respondents are the managers of companies. There were 126 companies that were surveyed and the total of 100 had completed questionnaires returned as the final sample. Three hypotheses have been developed through literature review and tested using Multiple Regression Analysis. The results show that Information Technology which consists of IT for administration, IT for communication, and IT for production has significant effect on competitive advantage. Competitive advantage is more influenced by IT for production than by both IT for administration and IT for communication.